2005
DOI: 10.1002/cbic.200500005
|View full text |Cite
|
Sign up to set email alerts
|

Development and Biological Evaluation of Potent and Specific Inhibitors of Mitotic Kinesin Eg5

Abstract: Monastrol was the first specific but moderate inhibitor of the mitotic kinesin Eg5 to be identified. It proved to be useful for studies of cell division and is thought to have anticancer potential. We have synthesized a small chemical library of monastrol analogues and tested them for Eg5 inhibition in vitro and for arresting mitosis of cultured cells. We found that dimethylenastron (1) is more than 100‐times more potent than monastrol in both cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
76
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(81 citation statements)
references
References 26 publications
(21 reference statements)
3
76
0
2
Order By: Relevance
“…This bipolar structure facilitates the ability of Kinesin-5 to interact with and slide adjacent microtubules during mitosis, thus contributing to the plus-end-directed force that is necessary to form and maintain the mitotic spindle (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Due to the importance of Kinesin-5 for mitosis, several studies have identified Kinesin-5 inhibitors (31)(32)(33)(34)(35)(36)(37)(38)(39)(40) that can be used in the treatment of cancer and other diseases of abnormal mitotic index (reviewed in refs 41 and 42).…”
mentioning
confidence: 99%
“…This bipolar structure facilitates the ability of Kinesin-5 to interact with and slide adjacent microtubules during mitosis, thus contributing to the plus-end-directed force that is necessary to form and maintain the mitotic spindle (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Due to the importance of Kinesin-5 for mitosis, several studies have identified Kinesin-5 inhibitors (31)(32)(33)(34)(35)(36)(37)(38)(39)(40) that can be used in the treatment of cancer and other diseases of abnormal mitotic index (reviewed in refs 41 and 42).…”
mentioning
confidence: 99%
“…The function of Eg5 in the mitotic spindle has been shown to be indispensable. Perturbation of its function prior to anaphase B by either antibody (1,11) or small molecule inhibitors (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) causes collapse of the bipolar spindle into a monoaster and leads to apoptosis in cells with intact spindle checkpoint machinery (24,25). As a result Eg5 has garnered substantial interest as a potential chemotherapeutic target in cancer treatment.…”
mentioning
confidence: 99%
“…Over the last decade, the effects of various Eg5 inhibitors on the proliferation of cancer cells have been investigated, and the mechanisms of action of several Eg5 inhibitors have been studied [7][8][9][10][11] . Dimethylenastron is a cell-permeable quinazoline-thione compound that acts as a potent inhibitor of Eg5 [12] . We have demonstrated previously that dimethylenastron inhibits pancreatic tumor growth by suppressing cell proliferation and resulting in robust apoptosis [11] .…”
Section: Introductionmentioning
confidence: 99%